2015
DOI: 10.1016/j.ijproman.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of project based organization: A case study

Abstract: Little research has been conducted on how project-based organizations navigate internal and external pressures to develop and improve project competences over time. Using a cases study approach, this paper examines the development and implementation of project based organization over a period of 30 years. Overall, the evolution of project management competencies in the organization broadly followed the prevailing approaches in improving organizational management practices uncovered in review of literature. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 44 publications
(50 reference statements)
0
37
0
6
Order By: Relevance
“…These projects therefore need to be aligned with strategy (Turner, 2016;Asrilhant et al, 2007), and this area looks at the how the degree of fit between PM and strategy is defined and measured (Martinsuo and Killen, 2014). Research has identified factors such as the top management support (Kwak et al, 2015). Research has also examined the effect of organisational culture on intra (Duffield and Whitty, 2015) and inter project knowledge flows and across organizations (Ghobadi, 2015).…”
Section: Structural Elements Of Project Capacitymentioning
confidence: 99%
“…These projects therefore need to be aligned with strategy (Turner, 2016;Asrilhant et al, 2007), and this area looks at the how the degree of fit between PM and strategy is defined and measured (Martinsuo and Killen, 2014). Research has identified factors such as the top management support (Kwak et al, 2015). Research has also examined the effect of organisational culture on intra (Duffield and Whitty, 2015) and inter project knowledge flows and across organizations (Ghobadi, 2015).…”
Section: Structural Elements Of Project Capacitymentioning
confidence: 99%
“…In this phase, it is recommended to formulate the internal project that will guide the projectification process, with a development focus from lower to higher levels of competence. That is to say, it starts with the planning of the development of the individual competences, going through the development and the continuous improvement of the organizational competences, until reaching the highest level of maturity desired; with the purpose, as suggested by Kwak et al (2015), of identifying the interconnection between improvement efforts and results [91].…”
Section: Discussionmentioning
confidence: 99%
“…This concept began to be recognized 40 years ago (J. V. Carvalho et al, 2017). These models started to emerge when quality management practices were successfully implemented in manufacturing processes (Kwak et al 2015).…”
Section: Maturity Modelsmentioning
confidence: 99%